Financial performance of Bandar Lampung City Government (Comparing the accountability of two mayor periods: 2006 – 2010 vs 2011 – 2015) - Ferry Aryadi; Ayi Ahadiat; Ribhan Ribhan (International Journal of Financial, Accounting, and Management, 2020)
Purpose: The purpose of this research was to determine the significance of differences in financial performance, community welfare, and Gross Regional Domestic Product (GDP) of Bandar Lampung City in two mayor periods. Research Methodology: This study used secondary data obtained directly from the Lampung Provincial Representative Audit Board with a complete-time series of 10 years during the period 2006 – 2015. The research used region government financial performance, society welfare as measured by the human development index, Gross Regional Domestic Product (GDP) Based on Constant Prices as the variable. By one way-ANOVA to analyze technical data on this research. Results: There is no significant difference in the average financial performance in the form of effectiveness ratios, efficiency ratios, expenditure balance ratios, and government financial growth ratios of Bandar Lampung in two major periods. However, this research finds there is a significant difference in the average of social welfare as measured by the Human Development Index (HDI) and Gross Regional Domestic Product (GDP) of Bandar Lampung city in two major periods. This means that the Bandar Lampung City Government has not been able to properly maintain and increase its growth. Limitations: This research took a sample in this study only Bandar Lampung city, while in Lampung province there are 15 regencies/cities, and this research in conducting disparate tests using the Anova test. This research would be better if using more samples and using another test. Contribution: This study contributes to providing input and advice to the city government in making decisions related to the preparation and realization of the Regional Revenue and Expenditure Budget in the future. Keywords: Financial performance, Effectiveness, Efficiency, A harmony of spending, Financial growth